2021 IEEE/ACM Third International Workshop on Bots in Software Engineering (BotSE) 2021
DOI: 10.1109/botse52550.2021.00012
|View full text |Cite
|
Sign up to set email alerts
|

Identifying bot activity in GitHub pull request and issue comments

Abstract: Development bots are used on Github to automate repetitive activities. Such bots communicate with human actors via issue comments and pull request comments. Identifying such bot comments allows to prevent bias in socio-technical studies related to software development. To automate their identification, we propose a classification model based on natural language processing. Starting from a balanced ground-truth dataset of 19,282 PR and issue comments, we encode the comments as vectors using a combination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…However, several studies are dedicated to automatically identifying bot accounts in OSS repositories, [cf. 14,73,74]. Future studies can select these bot detectors to clean their dataset before training and testing their commit message generation models.…”
Section: Removing Irrelevant Commitsmentioning
confidence: 99%
“…However, several studies are dedicated to automatically identifying bot accounts in OSS repositories, [cf. 14,73,74]. Future studies can select these bot detectors to clean their dataset before training and testing their commit message generation models.…”
Section: Removing Irrelevant Commitsmentioning
confidence: 99%
“…We found that if there exist comments from others (other_comment), e.g., endusers or external developers, the pull request is more likely to be merged (Section 3.1.1). Different from Golzadeh et al [61], we validated on a much larger dataset and consider different kinds of projects instead of just Cargo ecosystem.…”
Section: Findings In Different Contextsmentioning
confidence: 99%
“…In a qualitative study limited to two OSS projects, it was found that the common, most frequent reason for rejection is unnecessary functionality [117]. In a quantitative study of 4.8K GitHub repositories and 1M comments, it was found that there are proportionally more comments, participants and comment exchanges in rejected than in accepted pull requests [114]. Another aspect of decision-making in code reviews is multi-tasking.…”
Section: Mcr Themes and Contributionsmentioning
confidence: 99%